2019
DOI: 10.1080/14739879.2019.1600383
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual care training and the GP curriculum: where to now?

Abstract: Recent work exploring GPs' attitudes to spirituality and spiritual care reveals that we are in an interesting period of development. Guidance from a range of sources including the UK National Health Service and the General Medical Council encourages person-centred approaches to spirituality and recognition of patients' spiritual dimension and concerns.(1-3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…A chaplain from Hamburg commented that the topics addressed by the instrument acquired "a depth and emotionality" that can hardly be dealt by the nursing staff and can hardly be adequately discussed without conversation training. This might be true and is a further argument for specific spiritual care training (O´Brien et al, 2019;Appleby et al, 2019;Alt-Epping et al, 2021). Staff´s spiritual care competences could be assessed with the Spiritual Care Competence Questionnaire (SCCQ) to identify training needs and to evaluate spiritual care training programs (Frick et al, 2019;Pastrana et al, 2021).…”
Section: Application Of the Instrumentmentioning
confidence: 99%
“…A chaplain from Hamburg commented that the topics addressed by the instrument acquired "a depth and emotionality" that can hardly be dealt by the nursing staff and can hardly be adequately discussed without conversation training. This might be true and is a further argument for specific spiritual care training (O´Brien et al, 2019;Appleby et al, 2019;Alt-Epping et al, 2021). Staff´s spiritual care competences could be assessed with the Spiritual Care Competence Questionnaire (SCCQ) to identify training needs and to evaluate spiritual care training programs (Frick et al, 2019;Pastrana et al, 2021).…”
Section: Application Of the Instrumentmentioning
confidence: 99%
“…Although in our study standardization did not seem to be desired, others promote more professionalization in order to make care for this dimension more transparent [ 45 ]. Appleby et al concluded their review by stating that if agreed it is desirable to encourage the integration of this dimension in general practice, we have to find common frameworks for these discussions [ 46 ], and a recent study amongst Scottish GPs even suggested to define a gold standard [ 47 ]. Wenham et al in a review proposed core content, aims and objectives to guide further work on this [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…(41) A recent study amongst Scottish GPs even suggested to de ne a gold standard. (42) We recommend research on ways of warranting integration of this dimension in care for palliative patients, without disregarding the GP as a professional in a person-centred approach. For example by exploring what kind of training suits GPs' needs.…”
Section: Theme 3 Practicementioning
confidence: 99%